Penerapan Model Pembelajaran Project Based Learning Untuk Eningkatkan Kualitas Pembelajaran Pada Mata Pelajaran Prakarya Dan Kewirausahaan Pada Siswa Kelas XI TKJ C Smk N 9 Surakarta Tahun Ajaran 2015/2016 - , Risyati; , Prof. Dr. Harsono, SU (2016)
The aim of this study is to improve the quality of learning process an subjects craft and entrepreneurship class XI TKJ C SMK N 9 Surakarta through the application of learning model project based learning. This study used action research approach with the classroom action research design. The study conducted in two cycles in which each cycle with 4 (four) step such as: (1) planning; (2) implementation; (3) observation; (4) reflection. The methods of data collection used the tests, observation, documentation and field notes. The analysis of technique data are used descriptive comparative and critical analysis. The results show that the skills of experienced teachers increase in the prior actions up to the first cycle and the second cycle. The original action skills, teachers get a score 17 with a success percentage of 42.5%. The first cycle with the acquisition score 27 has a success rate of 67, 5%. Then, the score increase again in the second cycle with the acquisition score 31 and with a success rate of 77.5%. Students' activities also increase from the prior action until the second cycle.The students' activity in the prior obtains a score 11.4 with a success rate of 28%. It increases in the first cycle with the acquisition score 23 with a success rate of 64% 26. Then, it increases again in the second cycle with the acquisition score 28 with a success rate of 78%. The increasing also occurs on student learning outcomes of prior actions to the implementation of the first cycle and the second cycle. Student learning outcomes in the spiritual attitudes and social behavior before action is 45% and 52%, then increase in the first cycle to the level of classical completeness 62% and 71%, and increase again in the second cycle to the level of classical completeness 70% and 85%. Learning outcome domains of knowledge shown by classical completeness before action is 34%, then increase in the first cycle of 59%, and increase in the second cycle of 76%. Improved learning outcomes realm of skills demonstrated by classical completeness before action is 38%, then increase in the first cycle with 79%, and increase again in the second cycle with 93%. It can be concluded that the learning model through project based learning can improve the quality of learning that includes the skills of teachers, student activities, and student learningoutcomes XI TKJ class C on the subjects of craft and entrepreneurship in SMK N 9 Surakarta. The advice given is that learning model of project-based learning can be used as a reference to the teacher as a solution to improve the quality of learning on the subjects of craft and entrepreneurship for students class XI TKJ C SMK N 9 Surakarta.